1989
DOI: 10.1002/gps.930040208
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and abuse in the elderly: Findings from the liverpool longitudinal study of continuing health in the community

Abstract: . SUMMARYProblem drinking and patterns of alcohol consumption are examined as part of a follow-up study of 1070 elderly subjects randomly selected from Liverpool general practitioner lists. Using a community version of the Geriatric Mental State Examination, the prevalence of current drinking problems was found to be 9.4/ 1000 subjects aged 65 and over. At follow-up three years later, one-third were drinking moderately and a similar proportion whose health had seriously deteriorated were abstinent. Detailed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…For example, in a sample of 1070 Liverpool residents aged 65+, less than one per cent abused alcohol. 6 A recent community survey in London revealed similar results. 7 In contrast, Bridgewater et al 8 found that 23% of men and 11% of women aged 60+ in a sample 101 general practice patients in Newcastle were classified as having alcohol problems.…”
Section: Incidence and Prevalencesupporting
confidence: 69%
“…For example, in a sample of 1070 Liverpool residents aged 65+, less than one per cent abused alcohol. 6 A recent community survey in London revealed similar results. 7 In contrast, Bridgewater et al 8 found that 23% of men and 11% of women aged 60+ in a sample 101 general practice patients in Newcastle were classified as having alcohol problems.…”
Section: Incidence and Prevalencesupporting
confidence: 69%
“…In men the figure was 5.7% [ 11. The decline in drinking with age is most marked in heavy drinkers and in men [1,9]. Decline of drinking with age has also been shown in a longitudinal study of elderly Liverpool residents [5].…”
Section: Hunter Area Mental Health Service Watt St Newcastle Nswmentioning
confidence: 89%
“…Non-drinking has been found to increase from 22% in the 30s to 47% in the 60s and around 80% in the over 80s [1,5]. Not only do fewer elderly drink regularly, but those who do are more moderate in their habits [6].…”
Section: Hunter Area Mental Health Service Watt St Newcastle Nswmentioning
confidence: 98%
See 2 more Smart Citations